2010
DOI: 10.1017/s1751731110000753
|View full text |Cite
|
Sign up to set email alerts
|

Royal jelly: can it reduce physiological strain of growing rabbits under Egyptian summer conditions?

Abstract: Exposure of growing rabbits to heat stress during summer adversely affects their performance leading to major production losses. A total number of 48 rabbits, unsexed V-line weaned rabbits, were randomly divided into four experimental groups, temperature ranged from high at 328C to low at 238C. Animals of the 2nd, 3rd and 4th group were individually orally given 200, 400 or 800 mg royal jelly (RJ)/kg BW once a week, respectively, to evaluate RJ ability to reduce physiological strain resulted from heat stress. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
17
2
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(30 citation statements)
references
References 26 publications
(17 reference statements)
8
17
2
1
Order By: Relevance
“…The medium dose (150 mg RJ/kg BW) had the highest beneficial effect compared to the lower and higher RJ doses. This indicates an improved kidney function The present results conform to those reported by Elnagar et al, (2010) in growing rabbits and Elnagar, (2010) in heat stressed male rabbits, which were treated with 200, 400 and 800 mg RJ/kg BW.…”
Section: World Rabbit Sci 22: 241-248supporting
confidence: 91%
See 3 more Smart Citations
“…The medium dose (150 mg RJ/kg BW) had the highest beneficial effect compared to the lower and higher RJ doses. This indicates an improved kidney function The present results conform to those reported by Elnagar et al, (2010) in growing rabbits and Elnagar, (2010) in heat stressed male rabbits, which were treated with 200, 400 and 800 mg RJ/kg BW.…”
Section: World Rabbit Sci 22: 241-248supporting
confidence: 91%
“…Our results are comparable to the results of Elnagar et al (2010) who reported that in stressed male rabbits, RJ led to a significantly increase in serum total protein, albumin and globulin. In contrast, RJ did not influence serum total protein, albumin and globulin in growing rabbits .…”
Section: Some Blood Biochemical Constituentssupporting
confidence: 91%
See 2 more Smart Citations
“…A maioria dos estudos que exploraram os efeitos biológicos da geleia real, em outros organismos além das abelhas, foi desenvolvida com animais experimentais. Alguns foram utilizados em experimentos visando posterior aplicação em seres humanos, entre estes estão os coelhos (Elnagar et al, 2010). De maneira benéfica, a comprovação científica dos efeitos da geleia real na reprodução de animais experimentais pode ampliar as possibilidades de estudos referentes aos seus efeitos em seres humanos, em animais elites de produção, bem como para conservação de espécimes silvestres em extinção ou com problemas de reprodução em cativeiro.…”
Section: Introductionunclassified